2023
DOI: 10.3389/fmicb.2023.1036386
|View full text |Cite
|
Sign up to set email alerts
|

Deep longitudinal multi-omics analysis of Bordetella pertussis cultivated in bioreactors highlights medium starvations and transitory metabolisms, associated to vaccine antigen biosynthesis variations and global virulence regulation

Abstract: Bordetella pertussis is the bacterial causative agent of whooping cough, a serious respiratory illness. An extensive knowledge on its virulence regulation and metabolism is a key factor to ensure pertussis vaccine manufacturing process robustness. The aim of this study was to refine our comprehension of B. pertussis physiology during in vitro cultures in bioreactors. A longitudinal multi-omics analysis was carried out over 26 h small-scale cultures of B. pertussis. Cultures were performed in batch mode and und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 69 publications
0
0
0
Order By: Relevance
“…A recent study (Anziani et al, 2023), performed a temporal multi-omics analysis on planktonic B. pertussis cells and identified that the genes and proteins involved in the TCA cycle from the conversion of ⍺-ketoglutarate to fumarate had relatively low activity until after 12 h. These reactions would have lower activity during activation of the glyoxylate shunt reinforcing the flux predicted in this study. Additionally, it was reported that the proteins and genes involved in glyoxylate metabolism decreased following 12 h before increasing again after 18 h and 45 min (Anziani et al, 2023). The extracellular metabolites that were measured also reinforced this trend (Anziani et al, 2023).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A recent study (Anziani et al, 2023), performed a temporal multi-omics analysis on planktonic B. pertussis cells and identified that the genes and proteins involved in the TCA cycle from the conversion of ⍺-ketoglutarate to fumarate had relatively low activity until after 12 h. These reactions would have lower activity during activation of the glyoxylate shunt reinforcing the flux predicted in this study. Additionally, it was reported that the proteins and genes involved in glyoxylate metabolism decreased following 12 h before increasing again after 18 h and 45 min (Anziani et al, 2023). The extracellular metabolites that were measured also reinforced this trend (Anziani et al, 2023).…”
Section: Discussionsupporting
confidence: 73%
“…Additionally, it was reported that the proteins and genes involved in glyoxylate metabolism decreased following 12 h before increasing again after 18 h and 45 min (Anziani et al, 2023). The extracellular metabolites that were measured also reinforced this trend (Anziani et al, 2023). Variation in the glyoxylate shunt has been observed in the biofilms of other species.…”
Section: Discussionmentioning
confidence: 75%